Ribothrypsis, a novel process of canonical mRNA decay, mediates ribosome-phased mRNA endonucleolysis - Ibrahim, Fadia; Maragkakis, Manolis; Alexiou, Panagiotis; Mourelatos, Zissimos (Nature structural & molecular biology, 2018)
mRNAs transmit the genetic information that dictates protein production and are a nexus for numerous pathways that regulate gene expression. The prevailing view of canonical mRNA decay is that it is mediated by deadenylation and decapping followed by exonucleolysis from the 3′ and 5′ ends. By developing Akron-seq, a novel approach that captures the native 3′ and 5′ ends of capped and polyadenylated RNAs, respectively, we show that canonical human mRNAs are subject to repeated cotranslational and ribosome-phased endonucleolytic cuts at the exit site of the mRNA ribosome channel, in a process that we term ribothrypsis. We uncovered RNA G quadruplexes among likely ribothrypsis triggers and show that ribothrypsis is a conserved process. Strikingly, we found that mRNA fragments are abundant in living cells and thus have important implications for the interpretation of experiments, such as RNA-seq, that rely on the assumption that mRNAs exist largely as full-length molecules in vivo. Using Akron-seq, a novel approach that captures native 3′ and 5′ ends of capped and polyadenylated RNAs, Mourelatos and colleagues show that mRNAs are subject to repeated cotranslational endonucleolytic cuts at the ribosome exit channel.